Mechanistic aspects of chaperonin GroEL/ES function - Horovitz, Amnon (Henry Stewart Talks, 2007)
Chaperonin structure, The allosteric mechanism of GroEL and coupling between GroEL allostery and folding, The unfoldase activity of GroEL, The GroE reaction cycle, Update interview: GroEL clients and frustration, Update interview: GroEL/ES footballs vs. bullets
Updated at 2020/12/09